2013
DOI: 10.1093/icvts/ivt161
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes in 23 thoracic primitive neuroectodermal tumours: a retrospective study

Abstract: The primitive neuroectodermal tumours are aggressive neoplasms with poor prognosis. Early diagnosis and total surgical excision of localized tumours with neoadjuvant or adjuvant chemotherapy and radiation improved disease-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…The median age ranged from 1 (19) to 36 (25) years. A male preponderance was described in 14 studies (8,(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)(26). Nevertheless, there were a comparable 43 males and 46 females in the present study.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The median age ranged from 1 (19) to 36 (25) years. A male preponderance was described in 14 studies (8,(12)(13)(14)(15)(16)(17)(20)(21)(22)(23)(24)(25)(26). Nevertheless, there were a comparable 43 males and 46 females in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…Our review of the literature revealed 17 pPNET report series. The clinical features, treatments and outcomes of the reported patients, as well as the 89 in the present study, are summarized in Table III (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 94%
“…1,2 According to the 2013 WHO classification of tumours of soft tissue and bone, both Ewing's sarcoma (ES) and PNET have a similar gene-phenotype, which can strongly express CD99 and exhibit characteristic chromosomal translocation t (11;22) (q24;q12). 3 Hence, they should be viewed as the same tumours, and these tumours have similar clinical appearances, immunohistochemical features, cellular molecular characteristics and prognoses, differing from each other only in their degree of neural differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of clinical guidelines that establish standardized management contributes to an unfavorable prognosis and a limited survival rate (24) In our patient's case, initial tissue biopsy was followed by neoadjuvant chemotherapy before surgical resection. This approach is supported by Sirivella et al 25), whose report suggests that the implementation of neoadjuvant chemotherapy led to an improvement in the 10-year survival free of disease indicator, observed in up to 84% of patients without metastases. Surgical resection is essential, and neoadjuvant chemotherapy leads to negative margins in 71% of cases, compared to 37% when surgical resection is the initial approach (26).…”
Section: Marinău Et Almentioning
confidence: 78%